(untitled) (Revista de Crítica Literaria Latinoamericana, 2011)
Analysis of Glauber Rocha’s film Cabezas Cortadas and its myriad of possible links with literature, focusing particularly on the film’s affinity with “dictator novels” and the director’s description of the film as “a Borgean journey through the work of Shakespeare”.